Structure‐Guided Design of a Group B Streptococcus Type III Synthetic Glycan–Conjugate Vaccine. Issue 31 (11th May 2020) - Oldrini, Davide; del Bino, Linda; Arda, Ana; Carboni, Filippo; Henriques, Pedro; Angiolini, Francesca; Quintana, Jon I.; Calloni, Ilaria; Romano, Maria R.; Berti, Francesco; Jimenez‐Barbero, Jesus; Margarit, Immaculada; et al.
Abstract: Invited for the cover of this issue is the group of Roberto Adamo at GlaxoSmithKline Research Center, Siena, and colleagues at The University of the Basque Country and Basque Research Technology Alliance. The image depicts a tactical plan with the different elements of the research as part of the team. Read the full text of the article at 10.1002/chem.202000284 . Abstract : " Our research is mainly driven by the understanding of polysaccharide portion responsible for immunogenicity in order to develop consistent alternatives to natural heterogeneous and structurally complex polysaccharides ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 7018 ff. (DOI: 10.1002/chem.202000284 ).